2021
DOI: 10.1093/ajcp/aqaa215
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence–Based Screening for Mycobacteria in Whole-Slide Images of Tissue Samples

Abstract: Objectives This study aimed to develop and validate a deep learning algorithm to screen digitized acid fast–stained (AFS) slides for mycobacteria within tissue sections. Methods A total of 441 whole-slide images (WSIs) of AFS tissue material were used to develop a deep learning algorithm. Regions of interest with possible acid-fast bacilli (AFBs) were displayed in a web-based gallery format alongside corresponding WSIs for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…Its positive component is almost 3 times bigger than the next largest one (263,000 positive patches in ours vs. 96,530 in Xiong et al’s dataset [ 15 ]), which is 429 times bigger than the smallest ones (506 in Zaizen et al’s set [ 20 ]). Our negative patches are 7 times more numerous than the second largest one of Pantanowitz et al [ 18 ] (7,000,000 vs. 1,111,918). Further applied augmentation techniques (both as position—rotations, shifts, crops, etc.—and in image properties—brightness, contrast, saturation, etc.)…”
Section: Introductioncontrasting
confidence: 45%
See 3 more Smart Citations
“…Its positive component is almost 3 times bigger than the next largest one (263,000 positive patches in ours vs. 96,530 in Xiong et al’s dataset [ 15 ]), which is 429 times bigger than the smallest ones (506 in Zaizen et al’s set [ 20 ]). Our negative patches are 7 times more numerous than the second largest one of Pantanowitz et al [ 18 ] (7,000,000 vs. 1,111,918). Further applied augmentation techniques (both as position—rotations, shifts, crops, etc.—and in image properties—brightness, contrast, saturation, etc.)…”
Section: Introductioncontrasting
confidence: 45%
“…Its validation is solely made on patches. Xiong et al [ 15 ] present a completely automated method of diagnosis while Yang et al [ 16 ], Pantanowitz et al [ 18 ], and Zaizen et al [ 19 ] developed AI-assisted diagnostic methods as a tool in the hands (and eyes) of pathologists. In Yang et al’s method, the pathologist evaluates a score heatmap superposed on the WSI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this study detected AFB using comprehensive AI screening despite negative results when AI was not used. Notably, Pantanowitz et al reported easier diagnosis using AI-assisted review, due to its higher sensitivity, negative predictive value, and accuracy compared with light microscopy and WSI evaluation without AI [24]. The current study showed that pathological diagnosis may be better at detecting AFB than traditionally indicated.…”
Section: Discussionmentioning
confidence: 55%